Physical properties of ultrasonic sprayed nanosized indium doped SnO2 films - Benouis, C. E.; Benhaliliba, M.; Yakuphanoğlu, Fahrettin; Tiburcio Silver, A.; Aida, M. S.; Sanchez Juarez, A. (Elsevier Science Sa, 2011)
Here, we report on the preparation and characterization of nanosized indium doped tin oxide films (TO:In). The films are grown by ultrasonic spray pyrolysis deposition (USPD) onto glass. The structural, optical, electrical and morphological properties of SnO2 (TO) films are investigated. The as-deposited films SnO2 have preferred orientation along the (2 0 0) plane and are polycrystalline with a tetragonal crystal structure. Following this direction, the average grain size, obtained from XRD patterns, decreases with the rate doping. It ranges from 64 to 17 nm. In UV spectrum, the transmittance increases followed by a slight decay within visible range. Optical band gap. E-g, is about 4.1 eV. The samples reveal a high resistivity which varies in the range 10(4)-10(7) Omega cm. Activation energies of shallow levels, as obtained from Arrhenius plots, vary from 85 meV to 165 meV. SEM and AFM analysis demonstrate nanostructure morphology. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Ultrasonic spray pyrolysis deposition; Growth of SnO2; Indium doping TO:In; High transparency; Nanosized morphology; AFM morphology; Power spectral density